Earthen Emitters - A New Concept for Micro-irrigation - Rana, S C; Naik, S C; Sahu, A P; Sharma, S D (Journal of Agricultural Engineering, 2001)
Experiments on hydraulics of four types of on-line earthen emitters of 10 cm length and 2 cm outside diameter, prepared by using sand, local clay and saw dust in different proportions; were conducted. The discharges of different types of earthen emitters placed above the soil surface i.e. in open air and of those placed in the soil and top flushed with the soil surface were determined under different heads. The wetting front advance at 30 min intervals for all types of earthen emitters were prepared. At the end of 150 min of each emitter testing, wetted soil samples were collected for moisture status determination. The results indicated that the emitter discharges increased with the increase of head and decrease of clay content in the emitter. The maximum horizontal diameter and the total depth of wetting front advance increased with the increase of elapsed time, head and decrease of clay content in the emitter. The peripheral moisture content was found to be more than the wilting point of the soil, thus, providing a suitable moisture regime to the root zone of crops for proper growth.